Cereus jamacaru seed germination and initial seedling establishment as a function of light and temperature conditions (Scientia Agricola, 2012)
Cereus jamacaru is a widespread Cactaceae of northeast Brazil, largely used as cattle food, and as ornamental and medicinal plant. Despite its distinguished importance, until now, there has been little information about the physiological aspects involved on its germination. The objective of this study was to evaluate the effect of light and temperature interaction on the seed germination and seedling establishment of this plant. The evaluated variables were germination percentage at 7 (% G7) and at 14 days after imbibition (% G14), germination average time index (GSI), germination average time (GAT), germination accumulated frequency (GAF), seedling dry mass and height. The highest % G14 and GSI were at 25 ºC in white light, whereas the highest GAT values were in darkness for all evaluated temperatures. On the other hand, % G14, GSI and GAF had the lowest values in darkness. Seeds germinated even in darkness, being however stimulated by the presence of light. The combination of white light and temperature of 25 or 30 °C is the most appropriate condition for seed germination tests.